Analisis Tingkat Kesiapan Sumberdaya Masyarakat Dan Pengaruh Produk Kredit Usaha Rakyat (KUR) Terhadap Perkembangan Usaha Mikro Kecil Menengah (UMKM) - Nasution, Thawap; Yulia, Rasty; Ningsih Puji Rahayu, Eka (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), 2024)
The development of the sharia economy in Indonesia continues to show a positive trend, with Indonesia ranked third in the Global Islamic Economy Indicator (GIEI) 2023. In Lampung Province, economic growth in the first quarter of 2023 of 4.96% also encouraged the strengthening of the small business sector, including MSMEs. This study aims to analyze the readiness of the community in accessing capital, as well as the impact of the People's Business Credit (KUR) product of Bank Syariah Indonesia on the growth of MSMEs. The study used a qualitative descriptive approach with a survey of 70 KUR customers of Bank Syariah Indonesia at the Bandar Lampung Tanjung Karang KCP for the period 2021–2023. The snowball sampling technique was applied in data collection, which was then analyzed using multiple regression with SPSS Version 22. The results of the study showed that community readiness had a significant influence on MSME growth, with increasing community readiness increasing the capacity of MSME businesses. In addition, the KUR product of Bank Syariah Indonesia has proven to be significant in supporting business development and access to capital for MSME actors.